PROBLEMATIKA PENDIDIKAN MODERASI DALAM PEMIKIRAN WAHBAH AL-ZUHAILI - Abdul Majid, Zamakhsyari; Mulyati, Mumun (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2022)
This paper aims to examine and analyze the problems education of Islamic moderation from the viewpoint of Wahbah al-Zuhaili's Tafsir al-Munir and al-Fiqh al-Islamiy wa Adillatuhu science. The focus of the study in this paper is to analyze the moderate thoughts of Wahbah al-Zuhaili in understanding Islam through Tafsir al-Munir. Wahbah al-Zuhaili as a Muslim intellectual who mastered various scientific disciplines and had a moderate perspective. Wahbah al-Zuhaili's thoughts on moderation in Islamic law through his work al-Fiqh al-Islamiy wa Adilatuhu. In the book of al-Fiqh al-Islamiy wa Adillatuhu, indicators of moderation in Islamic law are a) Flexibility in Islamic Law, b) Renewal in Islamic Law, c) Views in Schools.